Síntese e atividade biológica de butenolídeos naturais e análogos - Thaís Altoé Moreira (2019)
Butenolides, y-unsaturated lactones, are present in the structure of a large number of natural products such as nostoclides, rubrolides, fimbrolides and cadiolides. These compounds come mainly from marine metabolites and present a wide array of biological activities as fungicide, bacterial, antibiofilm, anti-inflammatory, cytotoxic and regulating seed germination. There are several reported studies on the total synthesis, synthesis of analogues and biological activity of butenolides. Aiming to contribute to the study of this class of compounds, the focus of this work is the synthesis of different types of natural butenolides and analogues, as well as the analysis of their biological activities. Chapter 1 had as its objective the accomplishment of a brief and efficient synthesis of rubrolides R and S, since they were first isolated in 2014, and showed good antioxidant activity and antiviral activity against H1N1 influenza virus (Influenza A), respectively. This work was divided in two parts: one to obtain rubrolide S and another to obtain both rubrolides (R and S). The main synthetic steps are: Vilsmeier type bromination, aldol condensation, Suzuki cross coupling reaction followed by deprotection and cyclization(used only in the second part). The use of these methodologies allowed in the first part the synthesis of rubrolide S in 2 and 3 steps, respectively 52% and 64% overall yield from 4-bromofuran-2(5H)-one. And in the second part, the synthesis of rubrolides R and S in 3 (44% overall yield) and 4 (41% overall yield) steps, respectively, also from 4-bromofuran-2(5H)-one. An important result was the conversion of rubrolide R into S by cyclization. In Chapter 2 the synthesis of 18 analogues to the cadiolides was carried out and 16 of which are unpublished. These compounds were obtained from terminal alkynes and acid chlorides in three (methoxylated cadiolides) or four (hydroxylated cadiolides) steps andshowed good overall yields ranging from 11% to 47%. Initially, the terminal alkynes reacted with the acid chlorides by Sonogashira coupling, forming different ketoalkynes. These were subjected to Diels-Alder/retro-Diels-Alder reaction (DA/RDA), followed byhydrolysis, to obtain various lactones. The lactones were reacted with different aromatic aldehydes to form 13 analogues to the methoxylated cadiolides. Finally, the hydroxyls of the methoxylated analogues were deprotected and 5 hydroxylated analogs were obtained. The key step involves the DA/RDA reaction, since it generated regioselective products with yields amoung 36% to 79%. All analogues are being evaluated for their bacterial and antibiofilm activities. In Chapter 3 were synthesized 11 lactones, 4 lactams, and these compounds were evaluated for their antibiotic and inhibitory activities of bacterial biofilm formation. In thesynthetic route used, we highlight the Suzuki coupling, alkylidation and lactamization reactions. As the synthesis of these butenolides has already been published, this chapter had a greater focus on its biological activities, which were divided into two types of assay. In the first assay thirteen compounds were analyzed and eight were active against S. mutans biofilms without showing significant interference in bacterial viability. In addition, the more active showed an inhibition rate of 65%. In the second trial two lactones were incorporated into sPEEK (sulfonated poly-ether-ether-ketone), a polymer used in dental implants, and its bacterial and antibiofilm activities were analyzed. The planktonic growthof S. mutans around the sPEEK/antibiofilm agents was not affected, however, the antibiofilm activity increased significantly. Cytotoxic activity was still analyzed and this showed that sPEEK/antibiofilm agents did not present cytotoxicity, in addition to sPEEK/15a-b structure stimulate metabolic activity and fibroblast proliferation.